The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.reprotox.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Developmental cigarette smoke exposure II: Kidney proteome profile alterations in 6 month old adult offspring

Abstract: Cigarette smoke exposure (CSE) during gestation and early development suppresses the growth trajectory in offspring. In prior studies utilizing a mouse model of ‘active’ developmental CSE (GD1-PD21), low birth weight induced by CSE persisted throughout the neonatal period and was present at the cessation of exposure at weaning with proportionally smaller kidney mass that was accompanied by impairment of carbohydrate metabolism. In the present study, littermates of those characterized in the prior study were ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…In concert, hippocampus energetic pathways were compromised at the cessation of exposure at PD21 as well as in the adult offspring at maturity at age 6 months. In conjunction with our other studies of the impact of developmental CSE on the kidney and liver proteome profiles in adult animals at maturity [55, 56], as well as the prior studies of the impact of developmental CSE in juveniles (PD21) animals at cessation of exposure [5254], we propose that ongoing suppression of glucose availability is insufficient to support the normal level of energetic processes within the hippocampus into adulthood. We further propose that the deficits in memory and behavior observed in these identical offspring following extensive behavioral phenotyping [50] reflect energetic precursor scarcity in the hippocampus.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…In concert, hippocampus energetic pathways were compromised at the cessation of exposure at PD21 as well as in the adult offspring at maturity at age 6 months. In conjunction with our other studies of the impact of developmental CSE on the kidney and liver proteome profiles in adult animals at maturity [55, 56], as well as the prior studies of the impact of developmental CSE in juveniles (PD21) animals at cessation of exposure [5254], we propose that ongoing suppression of glucose availability is insufficient to support the normal level of energetic processes within the hippocampus into adulthood. We further propose that the deficits in memory and behavior observed in these identical offspring following extensive behavioral phenotyping [50] reflect energetic precursor scarcity in the hippocampus.…”
Section: Discussionsupporting
confidence: 61%
“…Tissues were harvested and stored at −80°C until analysis. Proteome profiling of hippocampus and other tissues was conducted on identically exposed littermates at the time of weaning (juveniles; PD21) [5254] and at adulthood (6 months of age) [55, 56]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteome profiling of the liver and other tissues was conducted on identically exposed littermates at the time of weaning (PD21) [5355]. The current report of liver proteome profiles from 6 month old animals that were previously developmental exposed to cigarette smoke serves as the lead manuscript for the coordinated three part evaluation of tissue specific proteome profiling studies, and includes the companion studies on kidney and hippocampus proteome profiles [56, 57]. …”
Section: Methodsmentioning
confidence: 99%
“…The present report details the impact of developmental cigarette smoke exposure on hepatic proteome profiles of offspring at 6 months of age – 5 months past cessation of their exposure – from littermates of pups from the same litters utilized in our prior study of developmental (GD1-PD21) cigarette smoke exposure. Parallel studies from our laboratory concerning the impact of such developmental CSE on liver, kidney and hippocampus proteome profiles at weaning (PD21) [5355] and at adulthood [56, 57] documented an impact of exposure on tissue metabolic activity. We previously reported that weanling (PD21) offspring who were developmentally exposed to cigarette smoke exhibited hepatic oxidative stress, impaired gluconeogenesis, altered lipid metabolism, impaired small molecule and amino acid metabolism, and impaired cellular morphology networks [54].…”
Section: Introductionmentioning
confidence: 99%